Fenomena Kompetisi Antar Kampung (Tarkam) Sepaktakraw di Kabupaten Blitar - Abdian Asgi Sukmana; M. Akbar Husein Allsabah (Journal Sport Area, 2018)
This study examined the descriptions and motives of the sepaktakrawinter-region (tarkam) that still exists today. It is a championship joined by various clubs throughout East Java. This reserachimplemented a qualitative descriptive form with a phenomenological approach in whichthe researchers explored various symptoms of the sepaktakrawtarkam activities. The data were obtained thorugh observations, interviews, documentation with a deep approach in the implementing group of the tarkamchampionship.This study found that the sepaktakrawtarkam championship administered in Blitarhad an overview about the administration, capital / activity costs, participants, tarkam rules that (1) administration is carried out by youth / community groups, (2) funding does not involve KONI institutions, but it is derived from sponsors and community self-help, (3) participants are various groups, namely adolescents / juniors, adults and ages above 35 years (orjokkapuk), (4) tarkam rules are set based on the agreement of participants and committee members, slightly referring to official rules. The motives for tarkam are (1) social / family motives (25%), (2) achievement motives (50%), (3) prestige motives or youth pride (5%) and (4) financial motives (10%).